Correlation and Interchangeability of Venous and Capillary Blood Gases in Non-Critically Ill Neonates - Tan, Ratna N. G. B.; Pauws, Steffen C.; van Loon, Evelyne; Smits, Vivanne E. H. J.; Lopriore, Enrico; te Pas, Arjan B. (Frontiers in Pediatrics, 2018)
Background Venous blood gas (VBG) is frequently used in the neonatal unit as alternative for capillary blood gas (CBG). However, studies reporting correlation are conflicting and data on interchangeability in neonates is lacking. Objective We investigated the correlation and interchangeability of the components between VBG and CBG in infants admitted to the neonatal intensive care unit. Methods In a prospective study in the neonatal unit in Leiden University Medical Center (Netherlands) simultaneously VBG and CBG were withdrawn in neonates when both venous puncture or intravenous access as blood gas monitoring was indicated. From each blood gas analysis, a Pearson correlation, intra class correlation and Bland-Altman analysis was performed. Clinically acceptable difference for each blood gas value was defined up-front by means of an absolute difference: pH +/-0.05; partial pressure of carbon dioxide (pCO2) (+/- 0.67 kPa=5mmHg); partial pressure of oxygen (pO2) (+/- 0.67 kPa=5mmHg); base excess +/-3 mmol/l; and bicarbonate (HCO3-) +/-3 mmol/l. Results In 93 patients (median gestational age 31 (IQR 29-34) weeks), 193 paired samples of VBG and CBG were collected. The Pearson correlation between VBG and CBG was very strong for pH (r=0.79;P<0.001), BE (r=0.90;P<0.001) and bicarbonate (r=0.87;P<0.001); strong for pCO2 (r=0.68;P<0.001); and moderate for pO2 (r=0.31;P<0.001). The percentage of the interchangeability within our acceptable absolute difference for pH was 88%, pCO2 72%, pO2 55%, BE 90% and bicarbonate 94%. Conclusion: Venous and capillary blood gas in neonates are well correlated and mostly interchangeable, except for pO2.